Pengolahan Data Penjualan Pakaian dengan Menerapkan Algoritma Apriori Data Mining - Harpad, Bartolomius; Lailiyah, Siti; Yusika, Andi (Forum Kerjasama Pendidikan Tinggi, 2024)
In its input, so far the use of sales transaction data has only been stored as an archive. In fact, the data can be utilized and processed into useful information to increase product sales or product innovation. In this case, sales data analysis needs to be carried out. With information about sales patterns, it can be seen what consumers buy most often. So from consumer purchasing patterns, decision making can also be done by the store related to the products to be sold. The data mining process in analyzing sales data, the Apriori algorithm can be utilized in the sales data process, namely by providing a relationship between sales transaction data. The data in question is sales data on clothes or pants that are ordered so that consumer purchasing patterns are obtained. Thus, the store can use the data to take suitable business actions. In this case, data can be used as a consideration to ensure the next sales strategy. The existence of information about sales patterns can find out what consumers buy most often. The products that are most often purchased by consumers are Hightwais Jeans Snow, Neda Tunik Full Buttons with 100% support for each product. by knowing the products that are most often purchased by consumers, the company can develop a strategy in determining the purchase of clothes and pants to maintain the availability of clothes and pants needed by consumers.